Analisis Akuntansi pada Piutang Usaha PT Asphalt Bangun Sarana Aspal Terhadap PSAK - Amalia, Zahra Zafirah (Jurnal Bisnis, Manajemen dan Akuntansi, 2025)
This journal article discusses the accounting treatment of trade receivables of PT Asphalt Bangun Sarana. PT Asphalt Bangun Sarana is a semi-manufacturing company in the asphalt processing industry. PT Asphalt Bangun Sarana makes sales to its customers, one of which is by credit sales, so that it will generate accounts receivable. PT Asphalt Bangun Sarana 's trade receivables consist of trade receivables from third parties and related parties. This analysis is carried out by checking the suitability of PT Asphalt Bangun Sarana 's accounting treatment related to recognition, measurement, recording, presentation and disclosure of PT Asphalt Bangun Sarana 's accounts receivable with the Statement of Financial Accounting Standards (PSAK). Based on the analysis that has been done, it can be concluded that the accounting treatment of PT Asphalt Bangun Sarana 's accounts receivable is in accordance with the accounting standards (PSAK) applicable in Indonesia.